The Role of Parental Involvement on Students’ Readiness in Early Bilingual Education: A Qualitative Exploration - Bakti, Windy Kurnia; Artini, Luh Putu; Padmadewi, Ni Nyoman (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
As more parents and educators see the value in raising bilingual children, bilingual schools are growing in popularity, offering dual-language instruction from an early age. In this situation children need a student readiness when they are mentally, physically and emotionally ready to learn. Therefore, student readiness is crucial. This study examines the role of parental involvement in the readiness of early bilingual students. Conducted in Doremi preschool Denpasar, Bali, the study used a qualitative method involving interviews and observations. This research involving six parents and their kindergarten children. The interviews were conducted based on six critical aspects outlined in Epstein’s parental involvement framework. Additionally, classroom behavior observations were made to evaluate the students from these representative parents. The findings reveal that parental involvement plays a significant role in early bilingual students’ readiness. High levels of parental involvement are associated with improved language acquisition, greater academic engagement, and smoother adaptation to the bilingual environment. Conversely, low levels of involvement often result in academic struggles and difficulties with language acquisition. To promote parental involvement, the study suggests strategies such as regular parent-teacher meetings and fostering a supportive home learning environment. These findings contribute to a better understanding of the impact of parental involvement in bilingual education and offer practical recommendations for schools and educators seeking to support early bilingual students more effectively